2005
DOI: 10.1111/j.1440-1746.2005.03826.x
|View full text |Cite
|
Sign up to set email alerts
|

Camostat, an oral trypsin inhibitor, reduces pancreatic fibrosis induced by repeated administration of a superoxide dismutase inhibitor in rats

Abstract: Camostat has a beneficial effect on pancreatic fibrosis induced by the administration of a SOD inhibitor, which inhibits the proliferation and activation of PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…In the case of targeting fibrosis in pancreatic tumor models, antibodies to CTGF, which activate PaSCs through their α 5 β 1 integrin receptor (44), inhibited tumor growth and metastasis in a xenograft mouse pancreatic tumor model (116,117). Agents showing benefit in experimental chronic pancreatitis include inhibitors of angiotensin II-converting enzyme and antagonists of the angiotensin II receptor (50,108); vitamin E (118) and DA-9601 (119), which function as antioxidants; troglitazone and thiazolidinedione, which are PPARγ ligands (120,121); camostat, which is a serine protease inhibitor (62,122); the herbal preparation Saiko-keishito, which has antioxidant and antiinflammatory properties (123); and COX-2 inhibitors (124). In addition, strategies aimed at blocking TGF-β signaling pathways (113,125) have proved effective in reducing experimental pancreatic fibrosis in rodents.…”
Section: Potential Treatments For Pasc Disordersmentioning
confidence: 99%
“…In the case of targeting fibrosis in pancreatic tumor models, antibodies to CTGF, which activate PaSCs through their α 5 β 1 integrin receptor (44), inhibited tumor growth and metastasis in a xenograft mouse pancreatic tumor model (116,117). Agents showing benefit in experimental chronic pancreatitis include inhibitors of angiotensin II-converting enzyme and antagonists of the angiotensin II receptor (50,108); vitamin E (118) and DA-9601 (119), which function as antioxidants; troglitazone and thiazolidinedione, which are PPARγ ligands (120,121); camostat, which is a serine protease inhibitor (62,122); the herbal preparation Saiko-keishito, which has antioxidant and antiinflammatory properties (123); and COX-2 inhibitors (124). In addition, strategies aimed at blocking TGF-β signaling pathways (113,125) have proved effective in reducing experimental pancreatic fibrosis in rodents.…”
Section: Potential Treatments For Pasc Disordersmentioning
confidence: 99%
“…However, CM treatment in the present study was delayed and so is unlikely to interfere with the course of events triggered by bleomycin immediately after its delivery. Moreover, CM is efficient in the abovementioned experimental models of fibrosis affecting other organs, where fibrosis was induced by the administration of different agents (36,37,39,40), surgical procedures (38,41), or even spontaneously (42). Third, the collagen content might be overestimated in the Sircol assay (43).…”
Section: Original Articlementioning
confidence: 99%
“…Camostat mesilate is a synthetic inhibitor of various proteases including trypsin, plasmin, kallikrein and esterases, resulting in the relief of the pain associated with pancreatitis [8][9][10]. Moreover, it has been reported that gabexate, the same guanidine compound as camostat, reduces flow resistance of the sphincter of Oddi in dogs [30].…”
Section: Discussionmentioning
confidence: 98%
“…Camostat mesilate, a synthetic inhibitor of various proteases, inhibits enzymatic auto-digestion of the pancreas and has been used to control the pain associated with pancreatitis [8][9][10]. However, there have been no reports regarding the efficacy of camostat mesilate in a subset of patients with dyspepsia associated with endosonographic evidence of mild pancreatic disease [5,11].…”
Section: Introductionmentioning
confidence: 99%